Beyond Borders: The Role of the Indonesian Student Diaspora in Egypt in the Pursuit of Independence - Imam Rasikh Islami; Erasiah (Nur Science Institute, 2025)
Abstract This article aims to explain the contribution/role of the Indonesian student diaspora in Egypt as national ambassadors to bilateral relations between Indonesia and Egypt, especially for Indonesian Independence. The Indonesian student diaspora in Egypt has an important role in seeking the support of Arab countries, especially Egypt; this effort was made long before Indonesia's Independence. The spirit of renewal of Indonesian students was also influenced by the idea of renewal raised by Muhammad Abduh and his students. So that, since 1920. Approaching 1945, the student political movement was increasingly active, and efforts to approach soft diplomacy had been made, introducing Indonesia as a Muslim country that needed help from other fellow Muslims. This effort paid off with the Egyptian State officially declaring Indonesia's Independence, followed by other Arab countries. Keywords: diaspora, contribution, egypt, indonesian students REFERENCES Cairo, K. (n.d.). Indonesia-Egypt Bilateral Consultation 2019: Indonesia-Egypt Agreed to Increase Economic Cooperation between the Two Countries. Indonesian Diplomacy. (n.d.). Ministry of Foreign Affairs of the Republic of Indonesia. Fachir, A. (2009). Portrait of Indonesia - Egypt Relations (A. . Fachir (Ed.)). Embassy of the Republic of Indonesia Cairo. Fernando, J., Marta, R. F., & Hidayati, R. K. (2020). Reactualization of Indonesian diaspora students in maintaining the nation's cultural identity on the Australian Continent. Journal of Communication Studies, 8. Haris, A. H., & Othman, M. R. (2013). Contributions of Egypt Alumni in Education and Literature in Malaya and Indonesia, 1920s-1970s. International Journal of West Asian Studies, 5. https://doi.org/10.5895 Haris, A. H., & Othman, M. R. (2015). The Activities of Malay Students in Cairo 1920s to 1960s. Bachelor, 30. Hassan, Z. (1980). Diplomacy of the Indonesian Revolution Abroad. Bulan Bintang. Huda, N., & Afrita, J. (2023). The Importance of Arabic in Diplomacy and International Relations Education. Indonesian Journal of Education, 4. Laffan, M. (2004). An Indonesian Community in Cairo: Continuity and Change in a Cosmopolitan Islamic Milieu. Indonesia, 77, 1-26. Muqoyyidin, A. W. (2013). ISLAMIC EDUCATION UPDATE ACCORDING TO MUHAMMAD ABDUH. Journal of Islamic Education, 18. Rahman, S. A. (2007). Indonesian Diplomacy in Egypt and Arab Countries in 1947. Discourse, 9. Roff, W. R. (1970). Indonesian and Malay Students in Cairo in the 1920s. Indonesia, 9, 73. https://doi.org/10.2307/3350623 Sani, A. (2021). AL-AZHAR UNIVERSITY OF EGYPT AND POLITICS. AAl-Kaffah 9. Sari, A. M. (2024). Ambassador Lutfi encourages increased exports of Indonesian products to the Egyptian market. Antara: Indonesian News Agency. SD, H. A. (2017). Diaspora as Indonesia's Multi Track Diplomacy to Realize the Master Plan for the Acceleration and Expansion of Indonesia's Economic Development. Proyeksi - Journal of Social Sciences and Humanities, 22. Shinta, A. (2019). Improving Diaspora's Understanding of Archipelago Concept as an Effort to Make the 2019 General Election Successful. Journal of Lemhannas RI Studies. Syafitria, F., Andayani, P., & Emayanti, E. (2023). THE CONTRIBUTION OF THE INDONESIAN DIASPORA TO ECONOMIC COOPERATION, UMKM, IMPORT AND EXPORT, AND FOREIGN DIRECT INVESTMENT. WELFARE JOURNAL OF ECONOMIC SCIENCE, 4. Tunggal, A. R. (2019). Indonesia-Egypt Diplomacy: Darussalam Gontor and Al-Azhar University. Islamic World and Politics, 4. Widodo, Y. (2017). Indonesian Student Diaspora Media: Existence, Role, and Indonesian Spirit. Journal of Communication Science, 14. Wilandra, S. S. (2019). The Role of Indonesian Youth in Egypt in the Independence Revolution: A Case Study of Harun Nasution. الشرقاوي, م. (n.d.). اندونيسيا المعاصرة. مكتبة الانجلو المعاصرة.